The Female Mosquito's Quest for Blood: Implications for Disease Cycles - Stephanie L. Richards; Sheri L. Anderson; Chelsea T. Smartt (EDIS)
ENY855, a 4-page illustrated fact sheet by Stephanie L. Richards, Sheri L. Anderson, and Chelsea T. Smartt, tells the story of the female mosquito’s quest for blood and how it may affect our lives. It tells why only female mosquitos feed on blood, what makes a blood source suitable, why some people are more attractive than others, and why host preference is important for understanding endemic and emerging arthropod-borne disease cycle. Published by the UF Department of Entomology and Nematology, October 2009.